2019
DOI: 10.15561/18189172.2019.0503
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric characteristics of professional football players in relation to the playing position and their significance for success in the game

Abstract: Background: Football is a game in which anthropometric characteristics are important factors for specific player positions, where morphological characteristics differ in relation to the competitive level and the position in the game. Body composition is an important indicator of the physical fitness and general health of athletes so today its often discussed in scientific literature. The aim of the research was to determine the differences in the anthropometric characteristics of the professional football play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
(37 reference statements)
0
6
0
1
Order By: Relevance
“…the differences in stature between the defenders and forwards compared with the rest of the playing positions reflect the demands of those positions, with increased stature being an essential component of their success. Evidence suggested that anthropometric characteristics may impact on soccer success, with stature and body weight being advantageous for certain positions, such as goalkeepers, defenders, and attackers [24]. this study indicated that defenders and forwards were significantly taller and heavier than the rest of the playing positions, while their bF% was not significantly different, which implies that the increased body mass may be attributed to increased stature or increased muscle mass.…”
Section: Discussionmentioning
confidence: 55%
“…the differences in stature between the defenders and forwards compared with the rest of the playing positions reflect the demands of those positions, with increased stature being an essential component of their success. Evidence suggested that anthropometric characteristics may impact on soccer success, with stature and body weight being advantageous for certain positions, such as goalkeepers, defenders, and attackers [24]. this study indicated that defenders and forwards were significantly taller and heavier than the rest of the playing positions, while their bF% was not significantly different, which implies that the increased body mass may be attributed to increased stature or increased muscle mass.…”
Section: Discussionmentioning
confidence: 55%
“…The purpose of these methods is to determine the probability of achieving success and increasing sportsmanship. Methods of analysis of physical development (Podrigalo, Cynarski, Rovnaya, Volodchenko, Halashko, & Volodchenko, 2019;Joksimović, Skrypchenko, Yarymbash, Fulurija, Nasrolahi, & Pantović, 2019;Lilić, Joksimovic, D' Angelo, Karišik, Hamad, & Gardašević, 2020), psychophysiological characteristics (Volodchenko, Podrigalo, & Aghyppo, 2017;Wolska et The main criteria for dividing street workout athletes are age and training experience. In our opinion, the training experience is the most important.…”
Section: Discussionmentioning
confidence: 99%
“…Since all data are available on the official euro basket website, the study does not require ethical approvals and consent forms (Joksimović et al, 2020). BMI was calculated by dividing the body mass by the square height of the body in meters (Kubayi et al, 2017;Joksimović et al, 2019). This study analyzed the morphological parameters (Body height, Body mass, Body Mass Index) in players competing in the first leagues in Europe in the 2020/21 season.…”
Section: Methodsmentioning
confidence: 99%